Design and Test of E-LKPD based on Liveworksheets - Purnama Sari, Wardani; Khairunnisak, Khairunnisak; Wati, Wati; Rahmania, Meri (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research is motivated by the importance of digital-based teaching materials with the help of live worksheets in economic learning. The aim of this research is to determine validity based on aspects of appropriateness of content, language, presentation and graphics, as well as to determine the practicality of the E-LKPD being developed. This type of research uses the R&D (Research and Development) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model development design. The data collection instrument was in the form of a validity sheet which was filled in by 6 validators, where the results obtained were in the very valid category by fulfilling the content feasibility aspect of 98%, the linguistic aspect of 93.7%, the presentation aspect of 98.6% and the graphic aspect of 85%. Meanwhile, the valid E-LKPD was tested for its practicality by obtaining a percentage score from user responses by teachers of 97.5%, and an average percentage by students of 93.1% in the very good category. Based on the results obtained, it can be concluded that the live worksheet-based E-LKPD developed is very valid and can be applied in the learning process on employment material.